MORPHOMOLECULAR IDENTIFICATION AND SPATIOTEMPORAL DISTRIBUTION OF HARD TICKS INFESTING CATTLE: A LIVESTOCK AND PUBLIC HEALTH CONCERN IN SELECTED LOCALITIES OF DISTRICT SWAT, KHYBER PAKHTUNKHWA, PAKISTAN (The Research of Medical Science Review, 2025)
In Pakistan, ixodid ticks have a variety of distribution patterns. Globally, ticks are significant vectors of numerous diseases affecting people, livestock, and other animals. Tick infestations cause significant problems in Pakistan's livestock industry, the country's principal source of rural income. They significantly harm the cattle business by causing hide loss and spreading vector-borne diseases. The distribution and way of life of ticks are significantly influenced by factors like the climate, host accessibility, and the environment. From March 2022 to October 2022, this study was carried out in selected localities of the district Swat. By using a practical sample technique, 2217 ticks were collected from 561 infected cattle of diverse ages and genders. With the help of molecular techniques and morphological characteristics, tick identification was done down to the genus and species level. Three species were identified in which the most prevalent species was Rhipicephalus microplus (40.78%) followed by Hyalomma anatolicum (31.93%) and Hyalomma marginatum (27.29%). Several risk variables were significantly correlated with the prevalence of all ixodid tick species (age, gender, living conditions, area, etc.). The distribution of tick infestation by body region showed that external genitalia (34.93%) was the most popular location, followed by the udder (26.02%), neck and head regions (20.68%), ear and tail (9.63%), shoulder (6.78%), and rear legs (1.96%). Additionally, mature, frail, and female animals are more susceptible to a tick infection. In Swat, the cattle population was primarily infested by the cattle tick Rhipicephalus microplus, and the summer was the tick season with the highest tick load records. In the current investigation, genetic markers (16S rRNA, ITS2, and COX1) were used to successfully amplify the targeted genes of the three tick species. The study highlighted the importance of molecular methods in epidemiological, medical entomological, and parasitological research, as well as the control of tick-borne diseases, which will ultimately improve public safety and livestock health.